A fault ride through scheme for doubly fed induction generator wind turbine. Issue 3 (3rd July 2018) - Ling, Yu
ABSTRACT: This paper presents a coordinated control scheme for the doubly fed induction generator (DFIG) based wind turbine (WT) to enhance the fault ride through (FRT) capability. The coordinated FRT scheme includes: (1) an improved vector control strategy; (2) a crowbar protection circuit; (3) a DC-link chopper circuit, and their coordinated control. The improved vector control strategy introduces a compensation term reflecting the instantaneous stator voltage in order to limit rotor current during the voltage fault. The effectiveness of the proposed approach has been demonstrated through various simulation cases. The simulation results show that the coordinated scheme can not only improve the FRT capability of the DFIG WT, but also can minimise the occurrence of hardware circuits and reduce their effect on the DFIG WT.